Una introduccion al renacimiento de la taxonomia - Elsa Faugère; Isabelle Arpin (Revue d'anthropologie des connaissances)
The text shows how taxonomy, also called systematics, through the different approaches and techniques used (including barcoding) for the exploration and documentation of new species, engages in a struggle for survival in a context less influenced by the same limitations of the biodiversity to be studied than by the very organization of the discipline itself, such as the absence of specialists for certain taxa and geopolitical and intellectual property restrictions (as in the case of expeditions to countries in the South). The authors show the need to include researchers from disciplines such as the social sciences in biodiversity studies in order to transform and open up fields of research, thanks to the results obtained in the various naturalist expeditions. The text details the problems arising from the difficulties in establishing relationships of trust between systematicians and social scientists. These difficulties in the exchange of information and techniques threaten the attempt to take taxonomy out of the academic context and give the discipline the long-awaited renewal.